2013 IEEE 27th International Conference on Advanced Information Networking and Applications (AINA) 2013
DOI: 10.1109/aina.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

How to Build Random Key Pre-distribution Schemes with Self-Healing for Multiphase WSNs

Abstract: In this paper 1 , we propose a simple random key pre-distribution (RKP) scheme with self-healing for multiphase wireless sensor networks (WSNs) without even lightweight operations such as a hash function, in which the link compromised by node-capture attack in a WSN automatically self-heals with time. Our scheme can enhance the resiliency of existing RKP schemes by only updating the key pool of a server with time. As a result, processing of each sensor is still the same as in the RKP schemes. More interestingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
(18 reference statements)
1
12
0
Order By: Relevance
“…We can easily confirm that Equation is the extended form of P R o K by . Figure shows a comparison of the analytical result ( P S − R K P ) with simulation result ( R S ) in S‐RKP. We found that the resiliency (1 − P S − R K P ) = 82.3 % by Figure holds when δ = 100.…”
Section: Security Evaluation By Analytical Modelsupporting
confidence: 61%
See 3 more Smart Citations
“…We can easily confirm that Equation is the extended form of P R o K by . Figure shows a comparison of the analytical result ( P S − R K P ) with simulation result ( R S ) in S‐RKP. We found that the resiliency (1 − P S − R K P ) = 82.3 % by Figure holds when δ = 100.…”
Section: Security Evaluation By Analytical Modelsupporting
confidence: 61%
“…We evaluate this scheme employing the modeling method of RoK, that is, we estimate a constant value and replace it by j . Then, the ratio P S ‐ R K P in is defined by PSRKP=i=1m()1r=1Ec′′()1mP+(r1)δipi,SRKP1p0,SRKP,where Ec′′=P/2δ. We can easily confirm that Equation is the extended form of P R o K by .…”
Section: Security Evaluation By Analytical Modelmentioning
confidence: 77%
See 2 more Smart Citations
“…The proposed key scheme improves the network's ability to spring back to normal operation. Also, round synchronisation is eliminated in the network (Miyaji and Omote, 2013).…”
Section: Related Workmentioning
confidence: 99%